O comportamento do consumidor esportivo: um estudo sobre os fatores que influenciam o comparecimento do p??blico aos est??dios e arenas no Brasil - Silveira, Marcelo Paciello da (2015)
This study aimed to evaluate what factors influence the attendance of the public at stadiums and arenas in Brazil. The study sought to understand the different factors (identification with the team, satisfaction, loyalty, risk perception, involvement, motivation) that affect the attendance in stadiums and arenas in Brazil, measured through the ticket purchase intent for soccer match. The descriptive quantitative method structural was adopted as a methodological procedure and the research was carried out by sending electronic questionnaires. The structural equation modeling (SEM) was the option to characterize the factors and the analysis of partial least squares (PLS) to validate the hypotheses. The results showed that the higher the identification of the sports consumer to his team, the greater the impact on the satisfaction of going to the stadium, increasing their loyalty to the team, making this inter-relationship between these three constructs increase the purchase intention of tickets to a soccer match. In addition, it was found that the higher the perceived risk, the lower the intention to purchase tickets. It was also detected that the greater the involvement of consumer sports with soccer, the greater the intention to purchase tickets. The only construct that had no impact on purchase intent was the motivation. One of the main academic implications was the proof that the identification with the team can be a predictor of satisfaction, and the inter-relationship between the constructs identification with the team, satisfaction to go to the stadium and loyalty to the team has high impact at the ticket purchasing decision by the sports consumer. Another academic implication was detected that the perception of risk negatively impacts the purchasing decision, even among fans who attend stadiums and arenas as well as the realization that the more involved with soccer fan is, the greater the impact on your decision to purchase tickets. Regarding to the managerial contributions, the main suggestion is to create a supporter's intelligence department in the structure of football clubs. This department would be responsible to measure, understand, create relationship with the fans and define strategies according to the level of identification, loyalty, satisfaction and involvement, always aiming to increase based revenues in the behavioral levels of each consumer group.